Supplement to the list of ancient coins discovered in Kampyr-tepe, Uzbekistan - Mielczarek, Mariusz; Nikonorov, Valerij P. (Acta Archaeologica Lodziensia, 2021)
Kampyr-Tepe, one of the most interesting North Bactrian sites of Hellenistic and post-Hellenistic times, situated on the right bank of Amu Darya river, has yielded a quantity of finds of Kushana coins. These coin-finds have been the basis for several studies on monetary circulation in the region, in which the 1995 study of E.V. Rtveladze holds a pre-eminent place. The present article consists of the publication of eight coins excavated in 1988-1991.